Role Of Acupuncture And Energy Medicine In The Management Of Diabetes Mellitus - A Case Report - Jayapal, Praveena; Sankar, Geethanjali; Venkateshwaran, S.T. (Indian Journal of Integrative Medicine, 2024)
Diabetes mellitus is a significant global health concern characterized by hyperglycemia due to insulin dysfunction. This case study explores the integration of acupuncture and energy medicine as adjunctive therapies for managing type 2 diabetes mellitus (T2DM). A 47-year-old female newly diagnosed with T2DM and grade 1 obesity presented with glycated haemoglobin (HbA1c 11.1%), accompanied by signs and symptoms of burning and itchy feet, polydipsia, polyuria, and stress-related issues. Acoording to traditional Chinese medicine diagnosis, kidney and spleen qi is deficient. Over 139 days, the patient received 45 sessions of acupuncture (every 3 days), focusing on points associated with diabetes management. Concurrently, she practiced daily meditation, prayer (including mantra chanting), and self-healing reiki. Lifestyle modifications included specific dietary changes and improvements in sleep hygiene. Results showed a significant reduction in HbA1c levels from 11.1% to 7.4%, along with decreased severity of foot burning sensation, improved sleep quality, enhanced energy levels, and better cognitive function. Pulse and tongue diagnosis according to Traditional Chinese Medicine revealed improvements in kidney and spleen function. Discussion highlights the potential of acupuncture and energy medicine in improving glycemic control and overall well-being in T2DM patients. These complementary therapies not only aimed to regulate blood sugar levels but also addressed mental and psychic health aspects associated with the disease. Mechanisms of action may involve immune modulation and metabolic regulation. Limitations include the small sample size and short follow-up period, suggesting a need for further randomized controlled trials to validate findings and optimize treatment protocols. Nevertheless, integrating acupuncture and energy medicine into conventional diabetes management offers promising benefits, potentially empowering patients and reducing healthcare costs. In conclusion, this case study underscores the potential of acupuncture and energy medicine as valuable adjunctive therapies in the comprehensive management of T2DM. Healthcare providers should consider these integrative approaches to enhance health outcomes and improve quality of life for individuals with diabetes.